Surface-engineered pH-responsive cobalt sulfide nanoszyme and preparation method and application thereof

CN122954967APending Publication Date: 2026-10-23SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147346.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

这种尺寸不仅限制了催化活性,还超过EPS基质的特征孔径,限制其渗入成熟生物膜,导致EPS瓦解不充分和抗菌效果受损

Benefits of technology

上述技术方案通过PEI表面工程化修饰,实现了硫化钴纳米酶的尺寸优化、分散性改善、表面电荷逆转和催化活性增强。PCoS纳米酶的平均粒径约为225 nm,显著小于未修饰的CoS(约652 nm),有利于渗入EPS基质并穿透成熟生物膜;PEI修饰使纳米酶表面带强正电荷(+37.9 mV),通过静电相互作用高效吸附于带负电荷的细菌表面,增强局部ROS介导的杀菌效果;PEI修饰提高了纳米酶中Co3+活性位点的比例,使其类氧化酶和类过氧化物酶活性较CoS提高2-3倍,且催化活性随pH降低而增强,在致龋酸性微环境中实现选择性激活。在抗菌机制方面,PCoS通过原位产生超氧自由基和羟基自由基,破坏细菌膜完整性,导致胞内ATP耗竭和蛋白泄漏,同时通过氧化修饰使胞内蛋白羰基化;转录组学分析显示PCoS处理扰乱了细菌的氨基酸生物合成、碳代谢和嘌呤代谢等关键代谢通路,实现膜损伤与代谢紊乱的协同杀菌效果。在抗生物膜方面,PCoS通过降解EPS中的多糖和蛋白质组分,显著降低生物膜生物量、厚度和不溶性EPS含量,有效瓦解成熟致龋生物膜。在体内应用中,PCoS在大鼠龋病模型中显著降低了光滑面和窝沟面龋损严重程度,保存了牙釉质结构,同时维持了口腔微生物的整体多样性,仅选择性抑制致龋菌群。采用的PEI为常用阳离子聚合物,CoS为具有良好生物相容性的钴基材料,细胞实验和动物实验均证实了PCoS的安全性。制备方法采用一锅溶剂热法,工艺简单、条件温和,适合规模化生产,因此具有良好的实际应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122954967A_ABST
    Figure CN122954967A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of nanobiomedicine and oral medicine, and particularly relates to a surface-engineered pH-responsive cobalt sulfide nanoscale enzyme as well as a preparation method and application thereof. Specifically, the nanoscale enzyme is a polyethyleneimine surface-modified cobalt sulfide nanoscale enzyme. The nanoscale enzyme has small size, good dispersibility, and a positive charge on the surface, and exhibits significantly enhanced dual activities of a class of oxidases and a class of peroxidases under acidic conditions, can be selectively activated in a cariogenic biofilm microenvironment, and realizes efficient antibiosis and biofilm removal. The results of the application show that the rationally designed PCoS nanoscale enzyme is expected to replace traditional antibacterial agents and be applied to caries prevention and treatment, and therefore has good practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanobiomedicine and oral medicine technology, specifically relating to a surface-engineered pH-responsive cobalt sulfide nanozyme, its preparation method, and its application. Background Technology

[0002] Dental caries is one of the most common chronic infectious diseases worldwide. Its occurrence and development are driven by a dysregulated cariogenic biofilm, in which acid-producing and acid-tolerant bacteria metabolize dietary carbohydrates to generate organic acids, leading to a persistently low pH microenvironment and progressive demineralization of the tooth hard tissue. Extracellular polymeric substances (EPS), mainly composed of insoluble dextran, proteins, and extracellular DNA, play a crucial role in biofilm structural integrity, bacterial adhesion, and antimicrobial resistance. Therefore, effectively disrupting the EPS matrix and selectively eliminating cariogenic bacteria under acidic conditions is a key challenge in dental caries management.

[0003] Traditional caries prevention strategies, including mechanical plaque removal, fluoride therapy, and chlorhexidine application, have shown clinical benefits, but are limited by issues such as lack of microenvironment responsiveness, insufficient biofilm removal, potential side effects, and poor patient compliance. In particular, most antimicrobial agents are less effective in acidic biofilms and cannot break down the EPS scaffold that protects bacteria.

[0004] In recent years, nanozymes, as nanomaterials with enzyme-like catalytic activity, have attracted attention as antibacterial agents due to their ability to generate reactive oxygen species (ROS) in situ. The ROS generated by nanozymes can simultaneously damage bacteria and extracellular polymers, overcoming biofilm-related tolerance and reducing drug resistance. However, current cobalt-based nanozymes are rod-shaped or elongated, with lengths reaching several micrometers. This size not only limits catalytic activity but also exceeds the characteristic pore size of the EPS matrix, restricting its penetration into mature biofilms, leading to insufficient EPS breakdown and impaired antibacterial efficacy. Furthermore, most cobalt-based nanozymes are negatively charged, hindering electrostatic adhesion to negatively charged bacteria. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a surface-engineered pH-responsive cobalt sulfide nanozyme, its preparation method, and its applications. Specifically, this invention utilizes PEI surface engineering modification to significantly reduce the size, improve dispersibility, reverse surface charge, and enhance the enzyme-like catalytic activity of the cobalt-based nanozyme while maintaining its good biocompatibility. This nanozyme selectively activates both oxidase-like and peroxidase-like activities in an acidic microenvironment, effectively adsorbing onto bacterial surfaces. It disrupts bacterial membranes by generating ROS, degrades EPS, and disrupts bacterial metabolism, thereby achieving highly efficient antibacterial and biofilm removal. Based on the above research results, this invention is thus completed.

[0006] To achieve the above-mentioned technical objectives, the present invention provides the following technical solution: A first aspect of the present invention provides a surface-engineered pH-responsive cobalt sulfide nanozyme, comprising: Cobalt sulfide (CoS) nanozyme core; And, a polyethyleneimine (PEI) coating modified on the surface of the nanozyme core; The PEI coating is introduced simultaneously via a one-pot solvothermal method, and the surface modification is completed during the CoS nanozyme synthesis process.

[0007] The PEI modification reduces the size of the CoS nanozyme from the micrometer level to the nanometer level. The hydration kinetic diameter of the nanozyme is 100-400 nm, preferably 200-300 nm, more preferably 210-250 nm; and most preferably, the hydration kinetic diameter is about 225 nm.

[0008] The PEI modification reverses the surface charge of the CoS nanozyme from negative (-25.4 mV) to positive (+37.9 mV).

[0009] The PEI modification enhances the Co content in the CoS nanozyme. 3+ The proportion of Co in the nanozyme increased (from 38.39% to 71.67%), thereby enhancing its dual catalytic activity as both an oxidase-like and peroxidase-like enzyme. Therefore, the Co content in the nanozyme... 3+ With Co 2+ The molar ratio is not less than 2.5:1, and more preferably 2.5:1-3.5:1.

[0010] The nanozymes exhibit significantly enhanced oxidase-like and peroxidase-like activities under acidic pH conditions (pH 2.5~4.5) and significantly reduced activities under neutral conditions, demonstrating pH-dependent catalytic characteristics, which is highly beneficial for their efficacy in the microenvironment of cariogenic biofilms.

[0011] A second aspect of the present invention provides a method for preparing the above-described surface-engineered pH-responsive cobalt sulfide nanozyme, the method comprising: S1. Dissolve polyethyleneimine (PEI), cobalt source and sulfur source in solvent and stir until homogeneous; S2. The mixed solution obtained in step S1 is subjected to solvothermal treatment to obtain PEI-modified cobalt sulfide nanozyme (PCoS).

[0012] The cobalt source can be cobalt acetate tetrahydrate.

[0013] The sulfur source can be thioacetamide.

[0014] The mass molar ratio of the polyethyleneimine, cobalt source, and sulfur source is 0.1-1:0.5-5:4-10 (g / mmol / mmol), preferably 0.4-0.6:0.5-1.5:6-8, and more preferably 0.5:1:7.

[0015] The solvent can be ethanol, and more specifically, anhydrous ethanol. The mixing process involves stirring for 0.5-5 hours, or more specifically, 1 hour.

[0016] The temperature of the solvothermal reaction is 130-170℃, more preferably 140-160℃, and most preferably 150℃.

[0017] The solvothermal reaction time is 2-6 hours, more preferably 2.5-3.5 hours, and most preferably 3 hours.

[0018] Preferably, the method further includes: after the reaction is completed, centrifuging to collect the product, washing it with water and ethanol, and redispersing it in deionized water for later use.

[0019] A third aspect of the present invention provides the use of the above-described surface-engineered pH-responsive cobalt sulfide nanozyme in the preparation of antibacterial or antibiofilm drugs.

[0020] In another specific embodiment of the present invention, the antibacterial or antibiofilm drug is used for the prevention and treatment of dental caries.

[0021] In another specific embodiment of the present invention, the nanozyme is selectively activated in an acidic cariogenic microenvironment, and generates superoxide radicals and hydroxyl radicals in situ through dual activities of oxidase-like and peroxidase-like enzymes, thereby clearing planktonic Streptococcus mutans and disintegrating mature biofilms.

[0022] In another specific embodiment of the present invention, the nanozyme can be used in combination with low concentrations of H2O2 to further enhance its antibacterial and anti-biofilm effects. Therefore, the application of the surface-engineered pH-responsive cobalt sulfide nanozyme in combination with H2O2 in the preparation of antibacterial or anti-biofilm drugs is provided.

[0023] Therefore, the antibacterial or antibiofilm drug has any one or more of the following effects: (a) Selectively eliminate cariogenic bacteria in an acidic microenvironment; (b) Degradation of extracellular polymers; (c) Disintegration of mature biofilms; (d) Used in combination with hydrogen peroxide to enhance antibacterial and anti-biofilm effects; (e) Selectively inhibit cariogenic bacteria while maintaining overall oral microbial diversity; (f) Reduce the degree of caries on the smooth and pit / fissure surfaces of the teeth.

[0024] The beneficial technical effects of one or more of the above technical solutions are as follows: The above technical solution achieves size optimization, improved dispersibility, surface charge reversal, and enhanced catalytic activity of cobalt sulfide nanozymes through PEI surface engineering modification. The average particle size of the PCoS nanozyme is approximately 225 nm, significantly smaller than that of unmodified CoS (approximately 652 nm), facilitating penetration into the EPS matrix and through mature biofilms. PEI modification imbues the nanozyme surface with a strong positive charge (+37.9 mV), enabling efficient adsorption onto the negatively charged bacterial surface through electrostatic interactions, thus enhancing the local ROS-mediated bactericidal effect. PEI modification also increases the Co content in the nanozyme. 3+ The proportion of active sites increases the activity of oxidase-like and peroxidase-like enzymes by 2-3 times compared to CoS, and the catalytic activity increases with decreasing pH, achieving selective activation in cariogenic acidic microenvironments. Regarding the antibacterial mechanism, PCoS disrupts bacterial membrane integrity by generating superoxide and hydroxyl radicals in situ, leading to intracellular ATP depletion and protein leakage. Simultaneously, it carbonylates intracellular proteins through oxidative modification. Transcriptomic analysis shows that PCoS treatment disrupts key metabolic pathways such as amino acid biosynthesis, carbon metabolism, and purine metabolism in bacteria, achieving a synergistic bactericidal effect of membrane damage and metabolic disturbance. In terms of biofilm resistance, PCoS significantly reduces biofilm biomass, thickness, and insoluble EPS content by degrading polysaccharide and protein components in EPS, effectively disintegrating mature cariogenic biofilms. In in vivo applications, PCoS significantly reduced the severity of caries on smooth and pit / fissure surfaces in a rat caries model, preserving enamel structure while maintaining overall oral microbial diversity, selectively inhibiting only cariogenic bacteria. The PEI used is a commonly used cationic polymer, and CoS is a cobalt-based material with good biocompatibility. Cell and animal experiments have both confirmed the safety of PCoS. The preparation method employs a one-pot solvothermal process, which is simple, mild, and suitable for large-scale production, thus possessing significant practical application value. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0026] Figure 1For the material characterization of PCoS in this embodiment of the invention, the following are included: (A) Transmission electron microscopy (TEM) image and EDS elemental mapping of CoS; (B) TEM image and EDS elemental mapping of PCoS; (C, D) Particle size distribution of CoS and PCoS; (E) X-ray diffraction (XRD) patterns of CoS and PCoS; (F) Fourier transform infrared (FTIR) spectra of CoS and PCoS; (G) High-resolution XPS patterns of Co 2p of CoS and PCoS; (H) High-resolution XPS patterns of S 2p of CoS and PCoS; (I, J) Surface potential mapping based on atomic force microscopy; (K, L) Surface potential distribution of CoS and PCoS; (M) Electrochemical impedance spectroscopy of CoS and PCoS; (N) Mott-Schottky curves of CoS and PCoS; (O) Particle size distribution of CoS and PCoS. The dispersion state at different time points in water and simulated saliva.

[0027] Figure 2 The following are characterization diagrams of reactive oxygen species (ROS) generated by PCoS in embodiments of the present invention, wherein: (A, B) electron paramagnetic resonance (EPR) spectra of superoxide anions and hydroxyl radicals generated by PCoS captured by DMPO in an oxygen atmosphere; (C, D) EPR spectra of superoxide anions and hydroxyl radicals generated by PCoS captured by DMPO in the presence of hydrogen peroxide; (E) ROS generation of CoS and PCoS detected by TMB probe in the absence of hydrogen peroxide; (F) ROS generation of CoS and PCoS detected by OPD probe in the absence of hydrogen peroxide; (G) ROS generation of CoS and PCoS detected by TMB probe in the presence of hydrogen peroxide. Generation status; (H) OPD probe detection of reactive oxygen species generation in CoS and PCoS in the presence of hydrogen peroxide; (I) Schematic diagram of PCoS dual-enzyme-like activity; (J, K) TMB detection of pH-dependent reactive oxygen species generation in CoS and PCoS in the absence of hydrogen peroxide; (L, M) TMB detection of pH-dependent reactive oxygen species generation in CoS and PCoS in the presence of hydrogen peroxide; (N) pH-dependent relative oxidase-like activities of CoS and PCoS in the absence of hydrogen peroxide; (O) pH-dependent relative dual-enzyme-like activities of CoS and PCoS in the presence of hydrogen peroxide; (P) Schematic diagram of pH response of CoS and PCoS.

[0028] Figure 3The following is a diagram of the antibacterial activity of PCoS in this embodiment of the invention, wherein: (A) typical agar plate photographs of Streptococcus mutans colonies after different treatments; (B) survival rate of Streptococcus mutans after different treatments; (C) Zeta potential of Streptococcus mutans after different treatments; (D) representative scanning electron microscope images and EDS element mapping of Streptococcus mutans after different treatments; (E) ATP content of Streptococcus mutans after different treatments; (F) concentration of extracted protein of Streptococcus mutans after different treatments; (G) protein carbonyl content of Streptococcus mutans after different treatments; (H) heatmap of distance between samples; (I) volcano plot of differentially expressed genes; (J) GO annotation analysis of differentially expressed genes of Streptococcus mutans after PCoS + hydrogen peroxide treatment; (K) KEGG enrichment analysis scatter plot; (LN) gene set enrichment analysis; (O) schematic diagram of the antibacterial mechanism of PCoS.

[0029] Figure 4 The following is an illustration of the anti-biofilm activity of PCoS in this embodiment of the invention, wherein: (A) catalytic activity of nanozymes in biofilm after different treatments; (B) biofilm stained with crystal violet; (C) representative scanning electron microscope images of biofilm after different treatments; (D) three-dimensional laser confocal images of Streptococcus mutans and the ratio of live to dead bacteria; (E) biofilm thickness; (F) dry weight of biofilm; (G) content of insoluble extracellular polymers; and (H) laser confocal images of caries-related biofilms after different treatments.

[0030] Figure 5 The following is an in vivo treatment effect diagram of PCoS in an embodiment of the present invention, wherein: (A) Schematic diagram of animal experimental protocol; (B) Representative photographs of caries lesions and plaque staining on the pit and fissure surfaces; (C) Representative photographs of caries lesions on the longitudinal section of the tooth; (D) Keyes scoring results of the smooth surface and pit and fissure surfaces of the tooth; (E) Micro-CT analysis; (F) Calculation of caries volume; (G) Chao1 index of oral microbiota; (H) Principal component analysis of oral microbiota; (I, J) Distribution of oral microbiota at the genus level. Detailed Implementation

[0031] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0032] It should be noted that the terminology used herein is for descriptive purposes only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof. Those skilled in the art can utilize other conventional techniques, methods, and reagents in the art based on the embodiments provided by this invention, without being limited to the specific embodiments of this invention.

[0033] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available. Unless otherwise specified, the experimental methods described are conventional methods in the art.

[0034] Example Materials and Methods Synthesis of CoS and PCoS CoS was synthesized via a hydrothermal method. In short, 1 mmol of cobalt acetate tetrahydrate and 7 mmol of thioacetamide were dissolved in 40 mL of anhydrous ethanol, magnetically stirred for 1 hour, followed by solvothermal treatment at 150°C for 3 hours. PEI-modified CoS (PCoS) was synthesized via a one-pot method, in which 0.5 g of PEI was added simultaneously with cobalt acetate tetrahydrate and thioacetamide during the solvothermal process. The product was collected by centrifugation, washed with water and ethanol, and redispersed in deionized water for subsequent experiments.

[0035] Surface characterization The morphology and size of CoS and PCoS were characterized using transmission electron microscopy (TEM, JEM 2100F, JEOL, Japan). Elemental composition and distribution were analyzed by energy-dispersive X-ray spectroscopy (EDS). Size distribution and zeta potential were tested by dynamic light scattering (DLS, Zetasizer NanoZS, Malvern, UK). X-ray diffraction (XRD) patterns were acquired on an X-ray powder diffractometer (AXS D8 ADVANCE, Bruker, Germany) at a scan rate of 10° / min in the range of 10–80°. X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) were recorded using a Thermo Nexus 670 spectrometer and an ESCALAB 250Xi (Thermo Scientific, USA), respectively. The surface potential of the nanozyme was characterized by atomic force microscopy (AFM, Bruker Dimension Icon, Germany). Electrochemical measurements were performed on a workstation (CHI 660E, CHInstruments, USA) using a standard three-electrode system. Mott-Schottky plots of CoS and PCoS were measured at 1 kHz using 0.5 mM Na2SO4 solution as the electrolyte.

[0036] Detection and identification of reactive oxygen species ROS generated by CoS and PCoS nanozymes were detected using electron paramagnetic resonance (EPR) spectroscopy (EMXplus-6 / 1, Bruker, Germany). PCoS was ultrasonically dispersed to obtain a 100 μg / mL suspension, which was then mixed with the appropriate spin trapping agent under N2 or O2 atmospheres, with or without H2O2. Specifically, •OH was detected using 50 mM DMPO in 0.1 M NaAc buffer (pH 4.5), while O2 was detected using 50 mM DMPO in methanol. •- ¹O2 was monitored using TEMP in 0.1 M NaAc buffer (pH 4.5). EPR signals were recorded at 0 and 10 minutes.

[0037] Evaluation of the activities of oxidase-like enzymes and peroxidase-like enzymes Oxidase-like activities were assessed by monitoring the oxidation of the chromogenic substrate under conditions without hydrogen peroxide (H2O2), while peroxidase-like activities were assessed under conditions with H2O2. To determine whether the nanomaterials generate ROS through oxidase-like and peroxidase-like activities, we used TMB and OPD as chromogenic probes for a two-substrate colorimetric assay. The reaction was carried out at room temperature in acetate buffer (NaAc, 0.1 M, pH 4.5). In a typical reaction mixture (total volume: 1 mL), the following components were added and thoroughly mixed: nanozyme suspension (final concentration: 100 μg / mL), TMB (DMSO stock solution 10 mM, final concentration: 1 mM) or OPD (ethanol stock solution 20 mM, final concentration: 0.2 mM), with or without H2O2 (final concentration: 1 mM). After 15 minutes of incubation, absorbance was measured at 652 nm (oxTMB) or 450 nm (oxOPD) using a UV-Vis spectrophotometer (UV-2600i, Shimadzu, Japan). Furthermore, the catalytic reaction was conducted at different pH values ​​representing physiological and cariogenic conditions. All experiments were repeated three times.

[0038] Cell culture The research protocol was approved by the Medical Ethics Committee of the Stomatological Hospital of Shandong University (No.: 202503027). Human dental pulp cells (hDPCs) were isolated from healthy donors' premolars / molars extracted for orthodontic treatment at the Stomatological Hospital of Shandong University. Human immortalized oral epithelial cells (HIOECs) were kindly provided by the Shandong Provincial Key Laboratory of Oral Tissue Regeneration. hDPCs (passages 2-7) were cultured in DMEM containing 10% FBS and 1% penicillin-streptomycin, while HIOECs were cultured in serum-free keratinocyte medium (KSFM), both in a humidified atmosphere at 37°C containing 5% CO2.

[0039] In vitro cytotoxicity assay hDPCs and HIOECs were divided into 5×10 3 Cells were seeded in 96-well plates and cultured overnight at 37°C, followed by co-incubation with gradient concentrations (0, 20, 40, 80 μg / mL) of CoS and PCoS for 1, 3, and 5 days. Cell viability was then assessed using the CellCounting Kit-8 according to standard procedures. Absorbance was measured at 450 nm using a microplate reader (SPECTROstar Nano, Germany). For live / dead staining, both cell types were seeded in 24-well plates, incubated with 40 μg / mL nanoparticles for 24 hours, and then stained with a live / dead staining kit. Cells were observed under a confocal laser scanning microscope (CLSM, Olympus FV3000).

[0040] In vitro hemolysis experiment The blood compatibility of the nanozyme was evaluated using a hemolysis test in rat blood. Blood was collected using heparin-anticoagulated tubes, and erythrocytes were obtained by centrifugation at 2000 rpm for 10 minutes. The collected erythrocytes were washed with physiological saline and diluted to a 4% (v / v) erythrocyte saline solution. Subsequently, gradient concentrations (0, 20, 40, 80 μg / mL) of CoS and PCoS were mixed with the erythrocyte saline solution and incubated at 37°C for 2 hours. Physiological saline and distilled water were used as negative and positive controls, respectively. The erythrocyte saline solution was centrifuged at 3000 rpm for 10 minutes, and the optical density (OD) of the supernatant was measured at 545 nm using a microplate reader (SPECTROstar Nano, Germany). The hemolysis rate was calculated using the following formula: Hemolysis rate (%) = (OD sample - OD negative) / (OD positive - OD negative) × 100%.

[0041] Bacterial culture Use Streptococcus mutans ( S. mutans NTCT 10449, a representative cariogenic bacterium, was cultured in an anaerobic workstation (Boxun, Shanghai, China) at 37°C in ultrafiltration (10-kDa cutoff; Millipore) tryptone-yeast extract (UFTYE) broth. The logarithmic growth phase bacterial suspension was adjusted to 10... 8 The concentration of colony forming units (CFU) / mL was used for subsequent experiments.

[0042] Antibacterial activity test The antibacterial efficacy of CoS and PCoS against planktonic bacteria was assessed by CFU counting. CoS or PCoS (40 μg / mL) was added to actively growing Streptococcus mutans (10 μg / mL) in NaAC buffer (0.1 M, pH 4.5) with or without 0.01 mM H2O2. 8 The bacteria were treated with CoS and PCoS (40 μg / mL) for 0.5, 1, and 2 hours, respectively, followed by serial dilutions and plating on UFTYE agar plates. For SEM, growing Streptococcus mutans was co-incubated with CoS and PCoS (40 μg / mL) for 1 hour with or without H2O2 (0.01 mM). The mixture was centrifuged at 6000 rpm for 10 minutes to collect the precipitate, which was then fixed with 2.5% glutaraldehyde. Subsequently, the bacterial samples were washed with PBS and treated with a gradient dehydration program of 30%, 50%, 70%, 90%, and finally 100% ethanol, each step lasting 15 minutes. Morphological changes of the treated bacteria were observed using scanning electron microscopy (SEM, Zeiss, Germany), and elemental surface distribution was analyzed by EDS. To investigate the bactericidal mechanism of the nanomaterials, the zeta potential of the bacterial-nanozyme mixture was tested by DLS.

[0043] Intracellular ATP content measurement Intracellular ATP levels were quantified to assess bacterial metabolic activity using a luminescence-based enhanced ATP chemiluminescence assay kit (E-BC-F201) following the manufacturer's instructions. In short, Streptococcus mutans (10 μg / mL) treated with CoS and PCoS (40 μg / mL) nanoparticles... 7 The lysate (CFU / mL) was sonicated on ice in ATP extraction buffer, and the lysate was centrifuged at 10,000 rpm for 10 minutes at 4°C. The supernatant was mixed with luciferase reagent under light-protected conditions, and the luminescence value was recorded using a microplate reader. The ATP content was calculated based on the standard curve.

[0044] Bacterial protein leakage assay and protein carbonyl content assay Streptococcus mutans (10) 7 Bacterial precipitates (CFU / mL) were incubated with NaAc (0.1 M, pH 4.5), CoS, or PCoS (40 μg / mL) in the presence or absence of 0.01 mM H2O2. Subsequently, bacterial pellets and supernatants were collected separately after treatment. Protein leakage in the supernatant was quantified using a BCA protein quantification kit. The bacterial pellet was resuspended in lysis buffer and sonicated on ice. The lysis buffer was centrifuged at 12,000 rpm for 10 min at 4°C, and the supernatant was collected. Protein concentration was determined using a BCA protein quantification kit. The concentration of the 2,4-dinitrophenylhydrazine (DNPH)-protein complex was measured spectrophotometrically at 370 nm using a protein carbonyl content assay kit, and the protein oxidation level was quantified according to the manufacturer's instructions.

[0045] Bacterial genome sequencing For RNA-seq analysis, *Streptococcus mutans* was co-cultured with PCoS and H2O2 at 37°C for 24 hours, and then the bacteria were collected for RNA-seq analysis on the Illumina platform by Shanghai Novogene Co., Ltd. Gene function was analyzed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Differential gene expression analysis was performed using the R package, and genes meeting the criteria of |log2 Fold change| ≥ 1 (p < 0.05) were considered differentially expressed genes (DEGs).

[0046] Biomembrane catalytic activity and staining Biofilms were treated twice daily by immersing them in 2.8 mL of 0.1 M NaAc solution (pH 4.5) containing CoS (40 μg / mL) or PCoS (40 μg / mL) or a control (buffer only) for 10 minutes, followed by gentle rinsing with physiological saline to remove unbound material. At the end of the experimental period (43 hours), samples from the H2O2, CoS+H2O2, and PCoS+H2O2 groups were exposed to 2.8 mL of 0.1 mM H2O2 for 5 minutes, while other groups were placed in NaAc buffer for 5 minutes. Biofilms were then collected for subsequent experiments. The catalytic activity of the nanozyme within the biofilm was assessed using a UV-Vis spectrophotometer at 652 nm using TMB working solution (0.1 M NaAc containing 1 mM TMB, pH 4.5). Crystal violet staining was performed to evaluate the in vitro anti-biofilm effect of the nanozyme. In short, the treated biofilm was gently rinsed with physiological saline to remove unbound bacteria, and then stained with 0.1% (w / v) crystal violet for 15 minutes. After rinsing off the unbound stain, the biofilm was photographed. Subsequently, it was eluted with 95% anhydrous ethanol, and the OD was measured using a UV-Vis spectrophotometer. 595 value.

[0047] In vitro biomembrane models and biomembrane disintegration Streptococcus mutans biofilms were established on dental slides or titanium substrates, vertically suspended in 24-well plates using a custom-designed wire scaffold to mimic the smooth surface of teeth. Each slide was pretreated with artificial saliva for 24 hours, then inoculated with 2 × 10⁶ microspheres. 5 CFU of *Streptococcus mutans* was suspended in UFTYE medium containing 1% sucrose. All samples were treated twice daily for 10 minutes in 2.8 mL of 0.1 M NaAc solution (pH 4.5) containing either CoS (40 μg / mL) or PCoS (40 μg / mL), or a control (buffer only). The culture medium was then changed twice daily until the end of the experimental period (43 hours). The H2O2-containing group was treated with 0.1 mM H2O2 for 5 minutes. After treatment, biofilms were collected and further characterized by SEM. Additionally, biofilms treated with the same protocol were dried in a laboratory oven at 37°C for 24 hours to determine their dry weight.

[0048] Live / dead staining of biofilms Biofilm live / dead staining assays were performed to assess bactericidal efficiency. The treated biofilms were gently washed twice with physiological saline and stained with equal volumes of SYTO 9 (Invitrogen, USA) and PI (Sigma-Aldrich, USA). The stained biofilms were observed under a confocal laser scanning microscope (CLSM, Zeiss, Germany), and their thickness was measured simultaneously.

[0049] Human-derived isolated natural tooth biofilm model and extracellular polysaccharide degradation experiment To further evaluate the preclinical anti-biofilm effect of nanoparticles, an in vitro biofilm model was established to verify the disintegration effect of nanozymes on cariogenic biofilms. In short, supragingival plaque biofilms were collected from children aged 36–72 months with severe early childhood caries (S-ECC). This study was approved by the Medical Ethics Committee of the Stomatological Hospital of Shandong University (No.: 202503027). Plaque was collected from the carious surface of the occlusal surface and immediately transferred to sterile Eppendorf tubes containing 1 mL PBS. The collected bacteria were vortexed and cultured in UFTYE medium at 37°C and 5% CO2. Biofilm growth and experimental treatment were as described previously. Subsequently, the anthrone method was used to quantify water-insoluble extracellular polysaccharides (EPS). In short, the collected biofilms were washed twice with physiological saline and centrifuged to obtain a precipitate. Double-distilled water was added to wash the precipitate to remove water-soluble EPS. Subsequently, 1 mL of 0.4 M sodium hydroxide (NaOH) was added to dissolve the residue, and then ethanol was added to precipitate the water-insoluble EPS. The collected supernatant was slowly added dropwise to a 0.2% anthrone solution in sulfuric acid and heated in a 95°C metal bath for 6 minutes. The absorbance of the solution was measured at 625 nm using a microplate reader at room temperature. Furthermore, the treated biofilm was gently washed with physiological saline and fixed with 4% paraformaldehyde at pH 7.4. The FISH oligonucleotide probes used in this study were Smu587, 5'-ACTCCAGACTTTCCTGAC-3' (Alexa Fluor 488 labeled, for Streptococcus mutans) and EUB 338, 5'-GCTGCTCCCGTAGGATG-3' (Cy3 labeled, for all bacteria). EPS was labeled with 1 μM Alexa Fluor 647-dextran conjugate. Samples were incubated at 46°C for 2 hours in a probe-containing hybridization buffer (0.9 M NaCl, 30% formamide, 20 mM Tris-HCl, 0.01% sodium dodecyl sulfate, pH 7.2). The samples were then washed with washing buffer (20 mM Tris-HCl, 0.2 M NaCl, 0.01% SDS, 5 mM EDTA) for 10 min. Additionally, the EPS of the samples was labeled with 1 μM Alexa Fluor 647-dextran conjugate (647 / 668 nm). Biomembrane structure was observed using CLSM.

[0050] Evaluation of in vivo caries prevention effect The animal research protocol was approved by the Medical Ethics Committee of the Stomatological Hospital of Shandong University (No.: 20220908). A total of 36 Sprague animals were used. Dawley (SD) rats (female, 15 days old, SPF grade) were housed in a specific pathogen-free environment. Before the experiment, the rats were examined to ensure they were free of Streptococcus mutans infection. Subsequently, the animals were orally infected with rapidly growing Streptococcus mutans for 3 consecutive days, and infection was confirmed by wiping biofilms on day 21. To better simulate actual conditions, the animals were treated with saline or nanozyme for 1 minute, followed immediately by treatment with / without 1 mM H2O2. All animals were randomly divided into six groups (n=6): (1) control group (saline, Ctrl), (2) CoS (40 μg / mL), (3) PCoS (40 μg / mL), (4) H2O2 (Ctrl + H2O2), (5) CoS + H2O2, and (6) PCoS + H2O2. Throughout the experiment, the rats' teeth received the above different treatments twice daily. All rats were fed cariogenic feed 2000 (Jiangsu Xietong Pharmaceutical Biotechnology Co., Ltd.) and 5% sucrose solution. Three weeks later, oral swabs were collected from each rat by gently wiping its teeth. These oral samples were preserved in DNA-free tubes. Stored at 80°C until microbiome analysis via 16S rRNA amplicon sequencing. After euthanizing rats, mandibular bones and major organs with teeth were collected. The mandibles were stained with 0.4% ammonium purpurate for 30 minutes, and images of the teeth were recorded under a stereomicroscope. The level of dental caries was assessed using micro-computed tomography (micro-CT), and scoring was performed using the Larson modified Keyes system. Caries scoring was performed by a calibrated examiner. Palatal and gingival tissues were collected and stained with hematoxylin and eosin (HE).

[0051] Results and Discussion Synthesis and Characterization of CoS and PCoS CoS and PEI-modified PCoS nanozymes were synthesized via a one-pot solvothermal method. TEM showed that PEI modification reduced the size of CoS. Elemental distribution plots confirmed the presence of nitrogen signals in PCoS, indicating successful PEI modification. Figure 1 A, B). DLS analysis further showed that, compared with CoS (~652 nm), PCoS maintained a significantly smaller hydration kinetic diameter (~225 nm) and a narrower size distribution ( Figure 1 C, D). XRD patterns show that the characteristic peaks of CoS almost disappeared after PEI modification. Figure 1 E). Zeta potential measurements showed a reversal of surface charge after PEI modification. CoS exhibited a negative surface potential (-25.4 mV), while PCoS showed a positive zeta potential (+37.9 mV). FTIR confirmed PEI functionalization, manifested in the characteristic NH stretching vibration, CN bending vibration, and Co-S stretching vibration in PCoS. Figure 1F). XPS analysis showed that the N 1s signal intensity of PCoS was significantly enhanced compared to CoS, confirming the successful immobilization of PEI. Co 2p3 / 2 spectra showed the presence of Co²⁻ in both samples. + and Co³ + Quantitative fitting analysis showed that Co³ in PCoS + The proportion of species (71.67%) increased compared to CoS (38.39%), while Co²... + The relative strength of species decreased from 61.61% to 28.33%. Figure 1 G). The S 2p spectrum shows the characteristic peaks of metal-sulfur bonding, as well as other features of the surface oxidation state ( Figure 1 H). Surface potential distribution maps based on AFM show that PEI modification reduces the surface potential of CoS from 0.712 V to 0.607 V (H). Figure 1 IL). EIS results show that the charge transfer resistance of PCoS is lower than that of CoS ( Figure 1 Mott-Schottky analysis showed that the flat-band potential of PCoS shifted from -0.30 V to -0.11 V relative to CoS. Figure 1 Furthermore, PCoS exhibited improved colloidal stability after 48 hours in water and simulated saliva environments (N). Figure 1 O).

[0052] Dual enzyme activity and pH responsiveness of PCoS First, EPR spectroscopy was used to detect the generation and type of ROS. PCoS generates significant superoxide radicals (O2 free radicals) in O2. •- The presence of H2O2 generates a strong hydroxyl radical (•OH) signal, indicating that it possesses dual OXD and POD enzyme activity. Figure 2 AD). Meanwhile, no singlet oxygen (¹O2) signal was detected. For example... Figure 2 As shown in E and 2F, PCoS catalyzes the rapid oxidation of both substrates, producing characteristic oxTMB and oxOPD absorption peaks, while CoS-induced substrate oxidation is weaker. The dual-enzyme activity was assessed by evaluating substrate oxidation in the presence of H₂O₂. Figure 2 As shown in GH, PCoS catalyzes the oxidation of TMB and OPD 2-3 times more strongly than CoS, indicating that PCoS has higher catalytic activity and can effectively degrade TMB and OPD. Figure 2 I).

[0053] To compare pH responsiveness, the relative catalytic activities of CoS and PCoS were quantified over a pH gradient. Both CoS and PCoS exhibited catalytic activity at pH = 4.5. Quantitative analysis showed that PCoS exhibited higher catalytic activity than CoS across the entire tested pH range, with the greatest difference observed at low pH (pH < 6). Figure 2 JM). Near neutral pH, the catalytic activity of both CoS and PCoS decreases significantly. Overall, as the pH decreases from neutral to acidic, PCoS exhibits stronger OXD and POD-like activities than CoS. Especially in the pH range of 2.5–4.5, the catalytic activity of PCoS is approximately 1.5–2 times higher than that of CoS. Figure 2 N-2P).

[0054] Antibacterial activity of PCoS First, the antibacterial activity of PCoS against Streptococcus mutans was evaluated using the CFU experiment. The results showed that the number of viable bacteria was significantly reduced after PCoS treatment, especially under H2O2 activation conditions. Figure 3 A). Time-dependent survival experiments showed that PCoS significantly reduced bacterial viability compared to CoS, with the most significant bactericidal effect observed in the presence of H2O2. Figure 3 B). After co-incubation, PCoS-treated bacteria exhibited a positive surface charge, while the negatively charged CoS-treated and untreated groups showed the opposite. Figure 3 C), indicating that PCoS adheres to the bacterial surface and aggregates into clusters. SEM images show that the control group and H2O2-treated group exhibit intact cocci morphology and smooth bacterial surfaces, while the PCoS-treated bacteria show obvious membrane deformation, surface collapse, and aggregation. Bacterial damage is more severe in the presence of H2O2. Elemental distribution maps further show the co-localization of cobalt and carbon signals on the bacterial surface, indicating a direct interaction between PCoS and bacteria. Figure 3 D). Intracellular ATP quantification showed decreased ATP levels in PCoS-treated bacteria. In the absence of H2O2, PCoS reduced ATP levels by approximately 50% compared to the control group. p<0.001), and the decrease was more significant after adding H2O2, exceeding 80% ( p<0.001) Figure 3 E). Meanwhile, protein leakage experiments showed that the extracellular protein concentration increased by approximately 2-3 times after PCoS treatment compared to the control group (with / without H2O2). p<0.001) Figure 3F) indicates impaired membrane integrity. Correspondingly, protein carbonylation levels significantly increased after PCoS treatment, especially under H2O2 activation conditions, reflecting extensive oxidative modification of intracellular proteins (F). Figure 3 G).

[0055] To elucidate how PCoS treatment reshapes bacterial biology under acidic conditions, transcriptome sequencing was performed on Streptococcus mutans exposed to H2O2 alone (as a control) or PCoS + H2O2. Figure 3 H). Based on the thresholds of |log2FC| ≥ 1 and p < 0.05, a total of 63 differentially expressed genes (DEGs) were screened, of which 25 were upregulated and 38 were downregulated (H). Figure 3 I). GO enrichment analysis compared PCoS+H2O2 with the control group, highlighting items related to oxidoreductase activity, α-amino acid metabolism, stress response, and redox processes. Figure 3 J). Furthermore, KEGG analysis revealed widespread perturbations in the metabolic network, including downregulation of secondary metabolite biosynthesis, microbial metabolism in different environments, histidine metabolism, carbon metabolism, and purine metabolism. Figure 3 K). Notably, GSEA further showed negative enrichment in amino acid biosynthesis, carbon metabolism, and microbial metabolism in different environments (K). Figure 3 LN). Therefore, after PCoS attaches to the bacterial surface, it generates ROS in situ, which kills bacteria through membrane damage and metabolic disorders. Figure 3 O).

[0056] The effect of PCoS on biofilm removal Quantitative analysis of TMB oxidation after co-incubation showed that PCoS exhibited higher catalytic activity than CoS within the biofilm, especially in the presence of H2O2. p < 0.001) Figure 4 A). Crystal violet staining showed that biofilm biomass decreased by approximately 60% after PCoS+H2O2 treatment. p < 0.001) Figure 4 B). To simulate the oral biofilm microenvironment in vivo, the experimental design is shown in the figure. SEM images show that the control group and the H2O2-treated group exhibit dense and continuous biofilm structures. In contrast, the PCoS-treated biofilm shows a disintegrated structure, with extensive collapse of the biofilm matrix, which is more pronounced in the presence of H2O2. Figure 4 C). Live / dead staining and 3D CLSM showed that PCoS treatment resulted in a large number of dead bacteria, an increased proportion of dead bacteria, and a significant reduction in biofilm thickness, especially in the presence of H2O2 (C). Figure 4D). Quantitative analysis further confirmed that the biofilm thickness in the PCoS+H2O2 group (<15 μm) was significantly reduced compared to the control group (~35 μm). p < 0.001) Figure 4 E). Correspondingly, the dry weight of the biofilm decreased significantly after PCoS treatment, especially under H2O2 exposure ( Figure 4 F). Fluorescent labeling further showed that PCoS treatment significantly reduced insoluble EPS within the biofilm (F). Figure 4 G). Furthermore, CLSM imaging of the more complex caries biofilm showed a simultaneous decrease in Streptococcus mutans and EPS after PCoS+H2O2 exposure, indicating the synergistic disintegration of the biofilm matrix and bacteria. Figure 4 H).

[0057] In vitro cell compatibility of PCoS The cytocompatibility of CoS and PCoS was evaluated using human dental pulp cells (hDPCs) and human immortalized oral epithelial cells (HIOECs). Cell viability was first assessed using the CCK-8 assay after incubation at different concentrations of CoS or PCoS for 1, 3, and 5 days. PCoS-treated cells showed significantly higher viability than the CoS-treated group throughout the entire concentration range tested. At concentrations of 20 and 40 μg / mL, the cell viability maintained by PCoS was comparable to that of the control group, with no statistically significant difference. Even at higher concentrations, PCoS-treated cells maintained approximately 80% acceptable viability. p < 0.001. In contrast, CoS induced a concentration-dependent decrease in cell viability, which was significantly reduced at higher concentrations on day 5 (especially in HIOECs). (p < 0.001). Cell integrity and viability were visually assessed by live / dead cell staining after 24 hours of exposure to 40 μg / mL CoS or PCoS. hDPCs and HIOECs showed extensive green fluorescence with negligible red signal in both the control and PCoS groups, while significant dead cells were detected in the CoS group. Hemocompatibility was evaluated using a erythrocyte hemolysis assay. The results confirmed that the hemolysis rate of both CoS and PCoS was less than 5%.

[0058] PCoS in vivo caries prevention effect The in vivo anti-caries effect of PCoS was evaluated using a rat caries model infected with Streptococcus mutans. Figure 5A). After different treatments, extensive caries and plaque accumulation were observed on smooth and pit / fissure surfaces in the control group and the H2O2 group, manifested as cavities and plaque staining. In contrast, PCoS-treated rats showed reduced caries severity, decreased plaque accumulation, smoother enamel surfaces, and fewer visible defects, especially when used in combination with H2O2. Figure 5 B). The Keyes score was used to visually grade caries lesions, classifying caries severity by the area of ​​discoloration on the tooth surface and the depth of discoloration in cross-section. Caries severity was categorized into four grades: enamel caries (E), mild dentin caries (Ds), moderate dentin caries (Dm), and extensive dentin caries (Dx). Results showed that caries in the PCoS-treated group was primarily confined to the enamel surface. In contrast, untreated / H2O2-treated animals exhibited deeper dentin damage (…). Figure 5 C). The scoring results showed that PCoS treatment significantly reduced the severity of caries at all stages. When combined with H2O2 treatment, the smooth surface score of the PCoS group was significantly lower than that of other groups ( p < 0.001) Figure 5 D). A similar trend was observed in pits and fissures, with significantly lower scores for moderate and extensive caries in the PCoS+H2O2 group. p < 0.001. Compared with the CoS+H2O2 group, the PCoS+H2O2 group had a 2-3 fold decrease in score (p < 0.001). p < 0.05).

[0059] Micro-CT was used to assess caries volume, mineral density, and demineralization depth. Three-dimensional reconstruction showed that PCoS-treated rats retained more enamel thickness and had reduced caries depth compared to the control and H2O2-treated groups. Figure 5 E). Quantitative analysis of caries lesion volume showed that mineral loss was significantly reduced in the PCoS group compared to the control and CoS groups, especially in the presence of H2O2 ( p < 0.001) Figure 5 F).

[0060] To evaluate the overall effects of different treatments on the oral microbiota and surrounding tissues, a comprehensive analysis of the oral microbiota was performed using high-throughput 16S rRNA sequencing. The Chao1 index was comparable between the control group and the PCoS+H2O2 group, indicating similar α-diversity of the oral microbiota. Figure 5 G). PCA showed partial separation of the microbial community, with the PCoS+H2O2 treatment group and the control group showing similar composition. Figure 5H). Analysis of the relative abundance of biofilms at the genus level showed a decrease in Streptococcus spp. ( Figure 5 I, J). Furthermore, no obvious damage or inflammatory response was observed in the surrounding soft tissues.

[0061] In summary, this invention develops a pH-responsive PCoS nanozyme engineered on a PEI surface for effective caries management. PCoS is activated by an acidic microenvironment, generating ROS in situ through OXD and POD-like activities. This localized, amplified oxidative stress scavenges EPS, disrupts bacterial membranes, and impairs metabolic pathways, ultimately inhibiting biofilm persistence and caries progression. These findings highlight the potential of well-designed PCoS nanozymes as alternatives to traditional antimicrobial agents for caries management. However, the long-term safety and genotoxicity of PCoS nanozymes require further comprehensive evaluation.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A surface-engineered pH-responsive cobalt sulfide nanozyme, characterized in that, include: Cobalt sulfide (CoS) nanozyme core; And, a polyethyleneimine (PEI) coating modified on the surface of the nanozyme core; The PEI coating is introduced simultaneously via a one-pot solvothermal method, and the surface modification is completed during the CoS nanozyme synthesis process.

2. The surface-engineered pH-responsive cobalt sulfide nanozyme as described in claim 1, characterized in that, The hydration kinetic diameter of the nanozyme is 100-400 nm, preferably 200-300 nm, and more preferably 210-250 nm; The surface charge of the nanozyme is positive.

3. The surface-engineered pH-responsive cobalt sulfide nanozyme as described in claim 1, characterized in that, Co in nanozymes 3+ With Co 2+ The molar ratio is not less than 2.5:1, preferably 2.5:1-3.5:

1.

4. The method for preparing surface-engineered pH-responsive cobalt sulfide nanozymes according to any one of claims 1-3, characterized in that, The preparation method includes: S1. Dissolve polyethyleneimine (PEI), cobalt source and sulfur source in solvent and stir until homogeneous; S2. The mixed solution obtained in step S1 is subjected to solvothermal treatment to obtain PEI-modified cobalt sulfide nanozyme.

5. The preparation method according to claim 4, characterized in that, The cobalt source is cobalt acetate tetrahydrate; The sulfur source is thioacetamide; The mass molar ratio of the polyethyleneimine, cobalt source, and sulfur source is 0.1-1:0.5-5:4-10, g / mmol / mmol.

6. The preparation method according to claim 4, characterized in that, The solvent ethanol is further defined as anhydrous ethanol.

7. The preparation method according to claim 5, characterized in that, The temperature of the solvothermal reaction is 130-170℃; the time of the solvothermal reaction is 2-6 hours.

8. The use of the surface-engineered pH-responsive cobalt sulfide nanozyme according to any one of claims 1-3 or the surface-engineered pH-responsive cobalt sulfide nanozyme prepared by the preparation method according to any one of claims 4-7 in the preparation of antibacterial or antibiofilm drugs.

9. The application as described in claim 8, characterized in that, The antibacterial or antibiofilm drugs are used for the prevention and treatment of dental caries.

10. The application as described in claim 8, characterized in that, The antibacterial or antibiofilm drug has any one or more of the following effects: (a) Selectively eliminate cariogenic bacteria in an acidic microenvironment; (b) Degradation of extracellular polymers; (c) Disintegration of mature biofilms; (d) Used in combination with hydrogen peroxide to enhance antibacterial and anti-biofilm effects; (e) Selectively inhibit cariogenic bacteria while maintaining overall oral microbial diversity; (f) Reduce the degree of caries on the smooth and pit / fissure surfaces of the teeth.